2019
DOI: 10.1136/bmjopen-2019-033623
|View full text |Cite
|
Sign up to set email alerts
|

Which urban land covers/uses are associated with residents’ mortality? A cross-sectional, ecological, pan-European study of 233 cities

Abstract: ​ObjectivesThe study aim was to determine whether the range and distribution of all, and proportions of specific, land covers/uses within European cities are associated with city-specific mortality rates.​Setting233 European cities within 24 countries.​ParticipantsAggregated city-level all-cause and age-group standardised mortality ratio for males and females separately and Western or Eastern European Region.​ResultsThe proportion of specific land covers/uses within a city was related to mortality, displaying … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…26 In Spain, Mueller and colleagues 21 estimated that around 60 deaths annually could be prevented in one neighbourhood of Barcelona by implementing the Superblocks Program and increasing the percentage of green space from 6•5% to 19•6% GA. 21 Furthermore, a large study examined the impact of land use or cover and mortality in 233 cities from 24 European countries and found a reduction in mortality in areas with more green spaces (ie, in cities in eastern and western Europe). 40 Open and public green spaces in cities (best represented by the %GA proxy) have been associated with increased physical activity levels, social interaction and social cohesion, psychological restoration (ie, stress reduction and attention restoration), and better general health and wellbeing. 1 Additionally, parks and larger green spaces provide ecosystem services by mitigating detrimental exposures, such as air pollution, noise, and the urban heat island effect.…”
Section: Discussionmentioning
confidence: 99%
“…26 In Spain, Mueller and colleagues 21 estimated that around 60 deaths annually could be prevented in one neighbourhood of Barcelona by implementing the Superblocks Program and increasing the percentage of green space from 6•5% to 19•6% GA. 21 Furthermore, a large study examined the impact of land use or cover and mortality in 233 cities from 24 European countries and found a reduction in mortality in areas with more green spaces (ie, in cities in eastern and western Europe). 40 Open and public green spaces in cities (best represented by the %GA proxy) have been associated with increased physical activity levels, social interaction and social cohesion, psychological restoration (ie, stress reduction and attention restoration), and better general health and wellbeing. 1 Additionally, parks and larger green spaces provide ecosystem services by mitigating detrimental exposures, such as air pollution, noise, and the urban heat island effect.…”
Section: Discussionmentioning
confidence: 99%
“…Past research on the potential influence of nature near citizens' residences on well-being has mainly investigated the association between nature and specific dimensions of well-being, such as its psychological (e.g., Mitchell, 2013;Pope et al, 2015;van den Berg et al, 2010;White et al, 2017;Wood et al, 2017) or physical (Olsen et al, 2019b;Richardson and Mitchell, 2010) aspects, or between nature and quality of life (Olsen et al, 2019a). To our knowledge, the potential effects of nature on well-being as a comprehensive concept have not been investigated.…”
Section: Research Contributionsmentioning
confidence: 99%
“…Second, the study deepens our understanding of the association between the "nature of nature" and well-being. The recent research conducted by Olsen et al (2019b) outlines differing associations between various urban land types and uses and mortality rates in European cities.…”
Section: Research Contributionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies, mostly focused on physical health outcomes, suggest close associations between dense urban environments with a lack of green spaces and poor health outcomes. For instance, two large-scale studies in multiple European and Chinese cities evaluated the association between urban form elements such as land covers and mortality ratios, finding that dense urban environments with a lack of green land covers were associated with a higher mortality [75,76]. Additionally, a study conducted by Xie, et al [77] in Wuhan, China, found that population density and building density were positively associated with stroke risk and, in contrast, a negative correlation between abundance of public parks and stroke risk, regardless of urban density.…”
Section: Health and Well-beingmentioning
confidence: 99%